Студенттерді кәсіби дайындауда халықтық педагогиканы пайдалану - Есімғалиева, Т.М.; Бозшолақова, А.У. (My University, 2013)
In article it is discussed directions of pedagogic and vocational training of the future experts, development of professional thinking, ability to live and work in modern life and achievements of the purposes by means of national pedagogic.